Personnel Standards for R&D Libraries and Information Centres - Narayana, G. J.; Desai, H. G.; Meera (Journal of Information and Knowledge, 1987)
Personnel standards for Defence R&D libraries and information centres have been formulated taking an interrelated, integrated, function-wise approach. Based on the concept of Standard Library Unit a work-to-staff relationship constant has been evolved. The concept of Standard Library Unit can be applied even to other types of libraries for formulating human resource norms. It is opined that personnel planning for libraries needs greater attention than given at present and the practice of entrusting charge of libraries to nonprofessionals as part-time assignments is harmful.